(untitled) - Givens, Charles J. (New York, 1988)
Givens assembles the ground rules of his fourth self-made fortune into 268 "strategies" for personal finance, taxes, and investment. His finance rules convey very helpful advice on insurance and credit, and a one-track plan for raising college money: Buy your child a house. Tax tactics stress heavy use of both common and exotic deductions, and the tax-saving virtues of owning a business. Investment ideas range from the prosaic, such as mutual funds and home ownership, to the questionable, such as tax lien purchases and the use of margin accounts.
Keywords: Finance, Personal,Tài chính cá nhân